The Influence of Service Quality and Customer Reference Groups on Consumer Buying Interest In PT. Valve Products. Rame Rekaguna Initiative - Nur Indriyani, Siwi; Irawati, Ike (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The aim of this research is to analyze the influence of service quality and customer reference groups on consumer purchasing interest in PT valve products, Rame Rekaguna Prakarsa. This type of research is included in the category of causal associative quantitative research. The research data source is primary data using a questionnaire with a 5 point Likert scale. The sampling technique used was a saturated sample. This research was conducted on 114 consumers of PT. Rame Rekaguna Prakarsa. The analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that service quality and customer reference groups, both partially and simultaneously, have a positive and significant effect on consumer buying interest in PT valve products. Rame Rekaguna Prakarsa. Results of testing data on service satisfaction and reference groups on interest in purchasing valve products at PT. Rame Rekaguna Prakarsa obtained Fcount (12,558) > Ftable (3.18) and a significance level of 0.000 < 0.05. This shows that the significance value of the simultaneous test (f test) was obtained at a value of 0.000, thus it can be concluded that there is a simultaneous influence between Service Quality and Reference Group Customers' interest in buying at PT. Rame Rekaguna Prakarsa. Based on partial research conducted on service quality on interest in purchasing valve products at PT. Rame Rekaguna Prakarsa obtained a significance value greater than α (0.166>0.05) and the calculated t value was smaller than t table (1.404 <1.675). This shows that service quality has no partial effect on interest in purchasing valve products at PT Rame Rekaguna Initiative. So that service satisfaction influences repurchase, or interest in repurchasing a product. Based on partial research conducted on the reference group regarding interest in purchasing valve products at PT Rame Rekaguna Prakarsa, the t count was 4.455, and the significance was 0.000. Therefore, the significance value is smaller than α (0.000>0.05) and the calculated t value is greater than the table (4.455>1.675). This shows that the customer reference group has a partial influence on interest in purchasing valve products at PT. Rame Rekaguna Prakarsa so it can be concluded that the reference group has a positive and significant effect on purchasing interest.